Wearable upper limb motion assist robot for eating activity - Kashtwari, Uzair; Zainul Azlan, Norsinnira; Shahdad, Ifrah (Research Centre of Mechanical Engineering Department Universitas Muhammadiyah Surakarta, 2020)
There are many people all around the world who are suffering from various type disabilities and need to depend on others to perform activities of daily living. One of the most important daily living activities is eating. The disabled should be able to eat their food independently at any time and place, without relying on the caregivers. This paper presents the development of a new wearable upper limb motion assist robot for helping the disabled to eat by themselves. The motion assist robot consists of two degree of freedom (DOF) motion, focusing on the two most important upper limb movements in eating activity, which are the elbow flexion/ extension and forearm pronation/ supination. A light-weight material is used for the fabrication of the wearable motion assist robot and Arduino is used as the microcontroller. The originality of the study is in terms of the design, operational sequence setting and kinematic analysis of the wearable upper limb motion assist robot that is specifically focusing on eating activity. The resulted prototype is portable, compact, light in weight, simple and low cost. The experimental results have proven that the proposed wearable upper limb motion assist robot for eating activity is successful in helping the users to perform the main upper extremity motions in eating. The success rate of the proposed system is 80% and it takes 6 seconds for the system to complete one feeding cycle.